PREDIKSI PROBABILITAS AUDIT DELAY DAN FAKTOR DETERMINANNYA - hersugondo -; Andi Kartika (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2013)
Time difference between financial statement and auditing opinion date indicates the amount of time needed in auditing settlement period. This condition can affect the punctuation of the information published and will influence market reaction towards the lengthy information. It will also the level of uncertainty based on the published information in the auditor’s financial statement in which containing company’s profit information. This study aims to measure the factors which affect audit delay. They are total asset, operation loss and profit, auditor’s opinion, profitability, solvability, and auditor’s reputation.The population of the study is the manufactaur companies registered in the Jakarta Stock Exchange in the period of 2006-2009. Sampling technique employed in this study is the purposive sampling with the total sample of 256 companies. The data analysis uses logistic regressions.The result of the study shows that the total asset and solvability have significant influence towards audit delay. On the other hand,  operation loss and profit, and auditor’s opinion profitability and the auditor’s reputation do not have any influence towards audit delay. Keywords: Audit Delay, the size of the company, operation loss and profit, auditor’s opinion, profitability, solvability, auditor’s reputation.